The Influence of Employee Performance Quality on the Quality of Probolinggo City's 112 Emergency Service - Nurul Jannah Lailatul Fitria; Shanty Bunga Adinda; Ferdy Aprilyandi (Austronesia Akademika, 2025)
Public administration emphasizes the dual role of government in regulation and service, with public services serving as a central indicator of good governance. In the context of emergency response, the quality of employee performance becomes crucial for ensuring effective service delivery. This study aims to analyze the influence of employee performance quality on the quality of the 112 emergency call service in Probolinggo City, Indonesia. Using a quantitative descriptive approach, data were collected through questionnaires, observations, and documentation from 100 respondents comprising government officials, academics, NGOs, and community leaders. The research employed Partial Least Squares (PLS) analysis to examine the causal relationship between employee performance quality and service quality dimensions, including reliability, responsiveness, assurance, tangibility, and empathy. The results demonstrate that employee performance quality has a significant and direct impact on the effectiveness of emergency services, with a path coefficient of 0.759, a p-value of 0.000, and a t-statistic of 1.690, confirming the proposed hypothesis. These findings highlight that improved employee capabilities, work processes, and enthusiasm positively enhance public trust and satisfaction in emergency handling. The study concludes that strengthening employee performance is a critical determinant for improving service quality in public emergency systems, supporting the broader goal of good governance and effective crisis management in Probolinggo City.